(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The study was conducted to demonstrate the factors that influence the organizational commitment of employees in the hospitality industry. Research data were collected using quota sampling, with a sample size of 220 employees working in the hospitality industry in Vietnam. Mixed research methods with a combination of qualitative and quantitative research are used to prove the research hypotheses. The structural equation modeling (SEM) was employed to indicate that the commitment to the organization of employees in the hospitality industry depends on 07 factors, including working conditions, nature of work, income and benefits, relationships with colleagues, leadership style, training and development, and corporate culture. Among these factors, working conditions and leadership style are the most important factors influencing employee engagement with the organization in the hospitality industry.